Product Derivation for Solution-Driven Product Line Engineering - Elsner, Christoph; Lohmann, Daniel; Schröder-Preikschat, Wolfgang (Proceedings of the First International Workshop on Feature-Oriented Software Development (FOSD 2009), 2009)
Solution-driven product line engineering is a project business where products are created for each customer individually. Although reuse of results from former projects is widely done, configuration and integration of the results currently is often a manual, time-consuming, and error-prone task and needs considerable knowledge about implementation details. In this paper, we elaborate and approach the challenges when giving automated support for product derivation (i.e., product configuration and generation) in a large-scale solution-driven product line context. Our PLiC approach resembles the fact that, in practice, the domain of a large product line is divided into sub-domains. A PLiC (product line component) packages all results (configuration, generation, and implementation assets) of a sub-domain and offers interfaces for configuration and generation. With our approach we tackle the challenges of using multiple and different types of configuration models and text files, give support for automated product generation, and integrate feature modeling to support application engineering as an extensive development task. Copyright 2009 ACM.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD4.produc
Keywords: Software Product Line; Feature Modelling